METODOLOGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK SISWA DI SMP PGRI 04 SIDODADI KABUPATEN MALANG - Siti Muawanatul Hasanah (PRODI PAI FIK UNIRA MALANG, 2025)
In the era of globalization, every human being must receive an education. Education is essential for human life, as it seeks to develop positive traits ad minimize negative ones, enabling humans to achive happines and peace in both this world and the hereafter. The ai of national education is to enlighten the life of the nation and develop the whole indonesian human being, namely a human being who believes in and is devoted to god almighty and has noble character, has knowladge and skill is physically and spiritualyy healthi, has a strong and independent personality and a sense of social and national responsibility. Improving morals is a primary mission for educational instutions. Therefore, methods are a highly influential component in education, particulary in relation to the process of developing students molars. The methods used by islamic reregious teachers in developing student morals will significantly influence their understanding and practice of moral values, particulary when they influence student awarness of practicing these noble valuaes.